2022
DOI: 10.1007/s00425-022-03865-8
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopy enables highly accurate differentiation between young male and female hemp plants

Abstract: Research activities involving the use of human subjects, vertebrate animals, and/or biohazards must be reviewed and approved by the appropriate Texas A&M University regulatory research committee (i.e., IRB, IACUC, IBC) before the activity can commence. This requirement applies to activities conducted at Texas A&M and to activities conducted at non-Texas A&M facilities or institutions. In both cases, students are responsible for working with the relevant Texas A&M research compliance program to ensure and docum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The spectra show prominent peaks that originate from various biological molecules present in plant tissues. 6,[10][11][12] Specically, vibrational bands centered at 520, 747 and 917 cm −1 can be assigned to carbohydrates, whereas the peaks at 1156, 1186, and 1525 cm −1 originate from polyene vibrations of carotenoids. 11,13 Carotenoids are pigments that play crucial roles in photosynthesis through the transfer of light, and have antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectra show prominent peaks that originate from various biological molecules present in plant tissues. 6,[10][11][12] Specically, vibrational bands centered at 520, 747 and 917 cm −1 can be assigned to carbohydrates, whereas the peaks at 1156, 1186, and 1525 cm −1 originate from polyene vibrations of carotenoids. 11,13 Carotenoids are pigments that play crucial roles in photosynthesis through the transfer of light, and have antioxidant properties.…”
Section: Resultsmentioning
confidence: 99%
“…9 Of present concern, Higgins et al (2022) used a portable Raman spectrometer to accurately identify the sex of mature hemp plants by scanning their leaves. 10 In this study, we aim to explore the potential of portable Raman spectroscopy for elucidating the sex of mature Palmer amaranth plants. The development of a rapid and accurate method for sex determination using a handheld Raman spectrometer would enable farmers, agronomists, and researchers to efficiently identify the sex of Palmer amaranth plants in the eld, facilitating the implementation of targeted management strategies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the peak at 1657 cm -1 could represent vibrations from an amide bond, characteristic of all proteins, or an alkene group in unsaturated fatty acids ( Khan et al., 2016 ; Farber et al., 2020 ; Farber et al., 2021 ). To accurately identify compounds and their functional groups, high performance liquid chromatography (HPLC) could potentially be applied ( Dou et al., 2021 ; Higgins et al., 2022 ). Previous utilization of HPLC coupled to mass spectrometry has successfully identified changes in the metabolic profile of the blood from patients diagnosed with early-stage LD ( Molins et al., 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…This difference in the concentration of lutein in male vs. female hemp plants can be detected by RS enabling confirmatory differentiation between such plants. It should be noted that RS can be also used to detect and identify biotic and abiotic stresses in plants [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. For instance, Sanchez and co-workers recently demonstrated that nitrogen, phosphorus, and potassium deficiencies, as well as salinity stresses, could be diagnosed in rice prior to their symptomatic appearances [ 24 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that RS can be also used to detect and identify biotic and abiotic stresses in plants [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. For instance, Sanchez and co-workers recently demonstrated that nitrogen, phosphorus, and potassium deficiencies, as well as salinity stresses, could be diagnosed in rice prior to their symptomatic appearances [ 24 , 26 , 27 ]. A growing body of evidence also suggests that RS can be used to phenotype species and their varieties and even differentiate between isogenic peanut varieties [ 28 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%